2013
DOI: 10.1002/mds.25789
|View full text |Cite
|
Sign up to set email alerts
|

Alimentary, my dear Watson? The challenges of enteric α‐synuclein as a Parkinson's disease biomarker

Abstract: An accurate early diagnostic test for Parkinson's disease (PD) is a critical unmet need. Recently, independent groups using different histological techniques have reported that the presence of alpha-synuclein (α-syn) in colonic biopsy tissue is able to distinguish living patients with PD from those without the disease. In addition, a further study has suggested that the presence of α-syn in colonic biopsy tissue may be evident in early or even prodromal PD. However, several questions remain regarding the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 41 publications
4
53
0
2
Order By: Relevance
“…We believe that the study reported here is a step in this direction. Harmonization of the terminology used to describe different reactivity patterns and their biological interpretation (physiological vs pathological) would be also needed, as has been recently discussed [18,25].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the study reported here is a step in this direction. Harmonization of the terminology used to describe different reactivity patterns and their biological interpretation (physiological vs pathological) would be also needed, as has been recently discussed [18,25].…”
Section: Discussionmentioning
confidence: 99%
“…4 Several recent studies of aSyn staining in colonic tissue from living patients with PD report sensitivities ranging from 72% to a remarkable 100%. [5][6][7] However, the description of some degree of aSyn labeling in controls in these studies and reports of aSyn in colonic tissue from individuals without PD have raised concerns regarding specificity. 8,9 The aim of the present study was to optimize the immunohistochemical detection of aSyn in colonic biopsies by adapting the paraffin-embedded tissue (PET) blot, a method developed to increase sensitivity and specificity of detecting aggregated proteins in a related proteinopathy, Creutzfeldt-Jakob disease.…”
Section: Methodsmentioning
confidence: 97%
“…As we and others have recently discussed, a key issue in using aSyn as a peripheral tissue PD biomarker concerns what signal is to be considered "pathologic" and what is "normal." 5,21 Many studies reporting lack of colonic aSyn staining in healthy individuals nevertheless note some degree of positivity that is labeled "normal" or "nonspecific." 6,7,22 Our study, along with other studies, would suggest that Ser129p-aSyn in healthy colon is not necessarily pathologic.…”
Section: Immunohistochemistry and Pet Blot Control Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several potential biomarkers have been pursued, ranging from neuroimaging to possible markers in the blood [19], CSF [20], and even the colon [21]. Specifically, molecular pathways related to a-synuclein, tau and b-amyloid peptides have received considerable attention.…”
Section: Biomarkers Of Disease Progressionmentioning
confidence: 99%